2020
DOI: 10.3390/ijerph17249427
|View full text |Cite
|
Sign up to set email alerts
|

Time Trends in Spain from 2001 to 2018 in the Incidence and Outcomes of Hospitalization for Urinary Tract Infections in Patients with Type 2 Diabetes Mellitus

Abstract: We aim to examine the incidences, clinical characteristics, and in-hospital outcomes of type 2 diabetes (T2DM) patients hospitalized with urinary tract infections (UTIs) in Spain and to identify the factors associated with in-hospital mortality (IHM). A retrospective observational study was carried out with a sample that included all adult patients who were hospitalized for UTIs between 2001 and 2018 and collected in the Spanish National Health System Hospital Discharge Database. We identified 850,276 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 37 publications
4
13
0
Order By: Relevance
“…We found that Escherichia coli was the most prevalent pathogen in both sexes regarding isolated pathogens, which is in line with previous reports [ 1 , 7 , 26 , 28 , 33 , 34 , 35 ]. However, the risk of IHM was associated with Staphylococcus aureus , but the risk decreased with other isolated pathogens, which is also observed among patients with COPD and type 2 diabetes mellitus [ 7 , 27 ]. Staphylococcus aureus bacteriuria is associated with bacteremia by this microorganism, which presents a complicated course with higher IHM [ 12 , 36 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…We found that Escherichia coli was the most prevalent pathogen in both sexes regarding isolated pathogens, which is in line with previous reports [ 1 , 7 , 26 , 28 , 33 , 34 , 35 ]. However, the risk of IHM was associated with Staphylococcus aureus , but the risk decreased with other isolated pathogens, which is also observed among patients with COPD and type 2 diabetes mellitus [ 7 , 27 ]. Staphylococcus aureus bacteriuria is associated with bacteremia by this microorganism, which presents a complicated course with higher IHM [ 12 , 36 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…The significant association between older age and higher incidence and IHM in patients with UTI observed here is supported by previous reports demonstrating that the risk of mortality increases in older ages [ 5 , 7 , 26 , 27 , 28 ]. It may be justified by the association between aging and a reduced innate and adaptive immune response, which is known as immune senescence [ 8 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations